Effects of auricular acupuncture stimulation on healthy adults’ upper limb motor-evoked potentials: A randomized, crossover, double-blind study - Zhang, Jin; Huang, Wen-Hao; Zheng, Ya-Dan; Li, Xin; Jiang, Hao-Xiang; Su, Min-Zhi; Huang, Xiao-Yan; Dou, Zu-Lin; Tang, Zhi-Ming (Frontiers in Neuroscience, 2022)
Objective The aim of this study was to determine whether auricular acupuncture has neuromodulatory effects on the motor cortex of healthy adults. Methods Fourteen healthy subjects received a real auricular acupuncture stimulation (SF1) session and a sham acupuncture stimulation session. The interval between the two types of stimulation was more than 24 h. A finger dexterity test (taping score and taping speed by using ipad) was assessed, and motor-evoked potentials (MEP) were assessed before and after each stimulation. Results Before the treatment, there were no significant differences in MEP amplitude, tapping score, or tapping speed (P > 0.05) between the real and sham stimulation conditions. After the treatment, the MEP amplitude, tapping score, and tapping speed in the real stimulation condition increased significantly compared to the pre-stimulation measurements and were significantly higher than those in the sham stimulation condition (P < 0.01). In the sham stimulation condition, the MEP amplitude, tapping score, and tapping speed decreased significantly compared to the pre-stimulation measurements (P < 0.05). Conclusion Acupuncture of auricular points can modulate the excitability of the motor cortex area of controlling the upper limbs. Clinical trial registration [http://www.chictr.org.cn/index.aspx], identifier [ChiCTR2100051608].